"language of instruction preference of junior secondary school students in Ijebu-Ode Local Government, Ogun State " (2014)
"This paper explains the importance of language among human beings especially in the classroom. It alludes to the national language policy in Nigeria that the language of the immediate community should be the medium of instruction in early primary education as it aids learner’s intellectual growth. It attempts to find out the language of instruction preference of junior secondary school students in Ijebu Ode Local Government Area, Ogun State. Three research questions were raised and a self-styled questionnaire, which reliability index is 0.63 was used to collect information. A total of six hundred and twenty four students, randomly selected from public and private secondary schools were used. Data collected were analyzed using descriptive statistics. Findings revealed that students prefer their mother-tongue as a medium of instruction (x 3.34; S.D. = 0.94) while some even prefer the mother-tongue as a medium of instruction in teaching science subjects (x 2.63; S.D. = 1.26). Their reason for preference of the mother tongue was because they understand better. This study, amongst others, recommends that mother-tongue should be encouraged in schools and teachers should combine mother-tongue and English in their lessons. It concludes that English as Nigeria’s official language could be enhanced through the use of the mother tongue . "